Sweet success with sweet potato - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Farmers in Africa achieve yields of about six tonnes per hectare from their crops of sweet potatoes. Elsewhere in the world, farmers expect twice that yield. By the year 2000 it is hoped that African farmers will be able to match those higher...